Effect of Different Retanning Agents on Shrinkage Temperature of Leathers - Zehra, Beena; Nadeem, Uzma; Ismail, Sarwat; Solangi, Barkat Ali; Pervez, Mohammad Kashif (Universitas Negeri Medan, 2023)
Retanning of tanned leathers played an important role to raise the shrinkage temperature characteristic and quantum of retanning agents, where crosslinks are formed with the polypeptide chain of the collagen or other reactive available sites of the collagen. This study is useful for the tanners to determine the percentage of shrinkage by using different retannages. The results revealed that the maximum thermal stability (increase in shrinkage temperature 21-25%) has been found in the basic chromium sulphate retanned leather without destruction of physical properties. Beside this, other types of retannages i-e, mineral retanning, phenolic based retanning, formalin based syntan have been showed thermal stability upto different levels (increase in shrinkage temperature 4-6%,12-15%, 10- 14% respectively) in addition to the development of physical properties such as tensile strength (N/ mm2 ), tear strength (N/mm), fullness , etc. to suit different needs.